Pengaruh Penilaian Kinerja Terhadap Produktivitas Kerja Pada PT. Jimmulya Palembang - Eno Yunitasari; Susi Handayani; Meilin Veronica (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effect of performance appraisal on employee work productivity at PT Jimmulya Palembang. The data used are primary data obtained from questionnaires and interviews. The research method used is simple linear regression analysis. The research results prove that the performance appraisal has a significant positive effect on employee work productivity. This research is expected to help companies to be able to increase employee productivity through employee performance appraisals